2022
DOI: 10.1097/ijg.0000000000002111
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Penetrating Canaloplasty in Childhood Glaucoma

Abstract: Penetrating canaloplasty was safe and effective for the management of refractory childhood glaucoma.Purpose: The purpose of this paper is to report the safety and efficacy of penetrating canaloplasty for the management of childhood glaucoma. Materials and Methods:This single-center prospective interventional case series enrolled 50 eyes of 32 patients with childhood glaucoma between July 2017 and July 2020. Penetrating canaloplasty to create direct communication between the anterior chamber and tensioning sutu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…[10,11] A small deep sclera helped keep the end of the incision of Schlemm canal open.Professor Liang and his team have reported that PCP demonstrated good safety and efficacy in eyes with primary angle-closure glaucoma, childhood glaucoma and corticosteroid-induced glaucoma. [10,[12][13][14] Here we demonstrated its good safety and efficacy in eyes with angle-closure glaucoma secondary to ICE. PCP could be considered as an option for the treatment of a wide variety of refractory glaucoma.…”
Section: Discussionmentioning
confidence: 93%
“…[10,11] A small deep sclera helped keep the end of the incision of Schlemm canal open.Professor Liang and his team have reported that PCP demonstrated good safety and efficacy in eyes with primary angle-closure glaucoma, childhood glaucoma and corticosteroid-induced glaucoma. [10,[12][13][14] Here we demonstrated its good safety and efficacy in eyes with angle-closure glaucoma secondary to ICE. PCP could be considered as an option for the treatment of a wide variety of refractory glaucoma.…”
Section: Discussionmentioning
confidence: 93%
“…“Childhood glaucoma,” a prevalent research topic, is characterized by a persistent increase in intraocular pressure, potentially leading to blindness. Surgical treatments for childhood glaucoma are a significant research area, encompassing procedures such as trabeculotomy ( 52 ), combined trabeculotomy-trabeculectomy ( 53 ), angio-atriotomy ( 54 ), Ahmed glaucoma drainage device implantation ( 55 , 56 ), Baerveldt glaucoma drainage device implantation ( 57 ), ciliary body photocoagulation ( 58 ), and XEN gel stent implantation ( 59 ), as well as penetrating otoplasty for refractory cases ( 60 ). Visual outcomes have been correlated with factors such as age at diagnosis, corneal clouding, and the presence of concurrent amblyopia ( 61 , 62 ).…”
Section: Discussionmentioning
confidence: 99%